Review on key generic technologies for railway converters - LIU Haitao; LIU Yongjiang; LI Hua; HE Guanqiang; PENG Xuanlin (机车电传动)
With continuous advancements in technology, customer requirements for converters, particularly quality indicators, are steadily increasing, driving the evolution of converters towards lighter weight, lower noise, higher reliability, and improved aesthetics. This paper delves into the key generic technologies in the design of converters for rail traffic, covering critical areas such as the application of power devices, lightweight design, vibration and noise reduction, electromagnetic compatibility, thermal management, and industrial design. It provides an overview of the current development status of these technologies both domestically and internationally, summarizes the challenges and difficulties encountered in their further development, and discusses in detail the core role these technologies play in enhancing product market competitiveness based on practical application examples. The findings provide comprehensive references and technical guidance for designing converters that are lighter, quieter, more reliable, and more aesthetically pleasing.